Failure to learn from safety incidents: Status, challenges and opportunities. (January 2018) - Stemn, Eric; Bofinger, Carmel; Cliff, David; Hassall, Maureen E.
Highlights: This literature review highlights where breakdowns in learning from incidents occur. The BTA method was applied as an analysis framework to distil collected literature. The analysis identified key issues confronting LFI and offered controls strategies. For LFI to occur, simultaneous interplay of several factors is required. A systematic well defined learning process must be instituted to identify lessons. The lessons identified must be disseminated broadly and embedded deeply. A just culture is a prerequisite to stimulate double-loop learning. It is recommended that the findings of the review be texted through field studies. Abstract: For effective and efficient learning to occur from safety incidents, certain factors and conditions related to the organisation, the actors or agents of learning, the learning process and the incidents themselves must be considered. Learning from incidents is not automatic and requires conscious and systematic steps to ensure it happens. Retaining the lessons learnt in the organisational memory to ensure continuous usage during the lifetime of the organisation is critical because personnel and learning agents change. To understand where breakdowns in learning from incidents are occurring, a bowtie analysis was used to organise the literature on failure to learn from safety incidents in a way that informs researchers and practitioners of priority areas. Additionally, the analysis aimed to test the validity of the bowtie method to filter failure to learn literature to identify key areas that could maximise learning. Using the bowtie analysis method led to the grouping of the issues identified in the literature on learning from safety incidents into three themes, namely, threats to failure to learn, consequences of failure to learn, and controls for overcoming failure to learn. This approach allows a summary representation of how and why failure to learn continues to occur together with potential practical strategies on how to overcome failure.